EFFECT OF AEROBIC TRAINING INTENSITY ON PHYSIOLOGICAL AND SKILL-BASED PERFORMANCE OUTCOMES IN UNDER-14 CRICKET PLAYERS - Tanveer Ali; Vikas Saxena (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study investigates the impact of aerobic training intensity on physiological and skill-based performance outcomes in under-14 (U-14) cricket players. Thirty male U-14 cricket players were randomly assigned to three groups: high-intensity aerobic training (HIAT, n=10), moderate-intensity aerobic training (MIAT, n=10), and a control group (n=10) for an 8-week intervention. Physiological outcomes (VO2max, resting heart rate, and anaerobic threshold) and skill-based outcomes (batting accuracy, bowling speed, and fielding efficiency) were assessed pre- and post-intervention. HIAT significantly improved VO2max (p<0.01) and anaerobic threshold (p<0.05) compared to MIAT and control groups, while both HIAT and MIAT enhanced batting accuracy (p<0.05). Bowling speed and fielding efficiency showed no significant differences across groups. These findings suggest that high-intensity aerobic training is more effective for improving physiological capacities in U-14 cricket players, with limited but positive effects on specific skill-based outcomes.